Thermoplastic Textile Fibers: Perspectives on Environmental Impacts and Innovations in Production and Recycling - Soares, Raysa Ruschel (2023)
Synthetic fibers are commonly used in the textile industry, especially polyester. It is used alone or blended with cotton fibers to produce fabrics with a PES-CO blend, widely used in clothing and decoration. Blended fibers, as they are a junction between natural and synthetic, carry the impacts of both productions. This research aimed to study the environmental impacts of thermoplastic and blended synthetic fibers, addressing the production and recycling of such fibers. For this, a research and analysis were carried out on the life cycle of pure and blended fibers of virgin origin, comparing with pure and blended fibers of recycled origin. It was possible to notice among the results, that the recycling of cotton and polyester fibers have the lowest environmental impact when compared with the production from virgin raw material and can be easily transformed into fabrics for the production of articles in the fashion industry. Blended polyester-cotton fibers are more difficult to recycle, but work with mechanical recycling and there are advances in chemical recycling, even if it is not yet applied on a large scale. After understanding how the production and recycling process works, a survey was carried out on the sustainability indicators that are used as a guide for the textile industry. As a large database was not found on the indicators focused on the Brazilian industry, an online search for companies that work with textile recycling or collection of textile waste was chosen to conduct interviews. Among the companies found, six structured interviews were carried out, five recyclers and one waste management and reverse logistics company. Analyzing the interviews, sustainability indicators were noted that have a greater weight in the impacts caused by the recycling process, such as the use of energy from clean sources. The use of sustainability indicators and the application of sustainability-oriented standards are essential to ensure cleaner production with less environmental impact, however, there is still difficulty for the sector to adapt to the proposed standards.